(untitled) (American Journal of Islam and Society, 2010)
The articulation of Islam with the new media, and the Internet in particular, has attracted the interest of many researchers. The Internet’s openness and democratic potential may infuse Islamic discourses with a new dynamic or, alternatively, offer a new lease of life to such valued traditions as shura (consultation) and ijtihad (independent thinking). Islam Dot Com belongs to the line of thought that seeks to discover how the Internet has been associated with Islam and the extent to which it may be thought to contribute to its democratization by providing a truly public sphere in which interested people can participate. On the other hand, the authors are cognizant of the limitations of the concept of “public sphere” when applied to Islamic contexts. Part of the book’s remit, therefore, is to examine how the Internet relates to shura, ijtihad, and ijma` (consensus). At the same time, it seeks to relate these theoretical arguments to an empirical case study consisting of a textual analysis of three Islamic websites: www.islamonline.net, www.amrkhaled. net, and www.islamway.com. The book’s structure comprises three theoretical chapters (chapters 1-3), two empirical chapters (chapters 4 and 5), and a concluding chapter (chapter 6) ...